Efficiency and Effectiveness of Islamic Microfinance toward Poverty Alleviation in Indonesia - Arif Rahman, Hakim (Universiti Malaysia Sarawak, 2024)
In the past few decades, Islamic microfinance has become pivotal in mitigating poverty, making it crucial to explore its operational effectiveness and performance within Muslim-majority nations. This research is centered on examining the efficiency and impact of Islamic microfinance in alleviating poverty across Indonesia. Employing a quantitative approach, the study utilizes Data Envelopment Analysis (DEA) to evaluate efficiency and panel data regression to determine effectiveness, drawing on data from 144 Islamic rural banks across 21 provinces. Initially, the results indicate that only 12 of these banks are performing efficiently, with the remaining banks showing variable efficiency levels across different provinces. Factors influencing efficiency include urban infrastructure, the density of microfinance institutions (MFIs), regional disparities, and the size of the Muslim population. Furthermore, the study underscores a stronger emphasis on financial performance over social performance among Indonesian MFIs. Despite variations in scale, the narrow gap between financial and social performance underscores the institutions' dedication to both sustainability and social objectives, aligning with the institutionalist perspective that influences sector practices in the region. Additionally, the analysis of effectiveness reveals critical insights. A notable inverse relationship between Total Financing (TF) and poverty levels highlights the importance of enhancing financial inclusion and expanding access to credit. Moreover, the management of Non-Performing Financing (NPF) emerges as crucial, correlating directly with rising poverty levels. The study also notes regional variations in how Financial Efficiency (FE) impacts poverty, emphasizing the need for targeted inflation management to support sustainable poverty reduction efforts.